Role of Olive Leaf Extract, Mesenchymal Stem Cells or Low Radiation Dose in Alleviating Hepatic Injury in Rats - Ola A. Gharib; Hanan A. Fahmy; Fatma Y. Abdou (SAGE Publishing, 2024)
Objectives This study was conducted to determine the efficacy of mesenchymal stem cells (MSCs) or low-dose gamma radiation (LDR) on liver injury compared to the effect of olive leaf extract as a hepatoprotective agent. Methods Rats were allocated into six groups; group I served as the negative control. Group II received 5% dextran sodium sulfate (DSS) in its drinking water for 1 week. Group III was injected with a single dose of 1 × 10 6 bone marrow-derived mesenchymal stem cells (BM-MSCs) intravenously. Group IV was treated as in group III after 5% DSS treatment. Group V was given 5% DSS, followed by olive leaf extract (OLE) (1000 mg/ kg, oral). Group VI: 5% DSS for 1 week, then was exposed to low-dose gamma radiation (LDR) (0.05 Gy). Results Rats treated with OLE, BM-MSCs, or exposed to LDR exerted significant alleviation in all hepatic biomarkers, significant enhancements in oxidative stress parameters, and improvements in inflammatory biomarkers Interleukin-1 beta (IL-1β) and Interferon gamma (INF-γ) hepatic contents compared with those of the DSS group. Histological pictures emphasized the biochemical findings. Conclusions BM-MSCs might be a valuable therapeutic approach to overcome hepatic injury. Exposure to LDR provided protective mechanisms that allow the body to survive better.